Effect Of Bid Ask Spread, Profitability, And Free Cash Flow On Earning Management - Nurainun Bangun (Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of bid ask spread, profitability, and free cash flow on earnings management. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling method used was purposive sampling with predetermined criteria. Earning management is determined by the accruals method. The results of this study stated that the bid ask spread did not have a significant effect on earnings management, while profitability and free cash flow had a significant effect on earnings management.